From Womb to World: Immunological Pathways Influencing Stunting and 2030 Sustainability - Nunuk Yuliastri (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
Stunting, which affects around 22% of children under five worldwide, is a serious public health issue that threatens the future of generations. Traditionally linked to poor nutrition, recent research shows that immune system imbalances and chronic inflammation also play a significant role in stunting, especially in low- and middle-income countries. This review examines how immune dysfunction and inflammation impact growth from pregnancy through early childhood, highlighting the importance of immune-related pathways in growth. Key findings reveal the significant influence of maternal immune health, neonatal immune activation, and recurrent infections on stunting. The review advocates for a shift in stunting prevention strategies, suggesting that integrating immune-targeted interventions with traditional nutritional approaches can more effectively address this issue. Policy recommendations include early health screenings to monitor inflammation and immune status, maternal supplementation with essential nutrients such as vitamin D and omega-3 fatty acids, and enhancing vaccination and breastfeeding practices. These strategies align with the United Nations’ Sustainable Development Goals, particularly those focused on hunger and health. By combining nutrition and immune system interventions, we can reduce stunting and ensure healthier futures for children globally.